A handbook for media librarians - Schopflin, Katharine ca. 20./21. Jh (Facet Publishing, 2008)
This edited collection provides a cutting edge overview of issues of key concern for information professionals providing information services in corporate environments. Corporate information professionals serving the workplace rather than learning communities or the general public face specific challenges and demands, from providing competitive intelligence to managing information in a global environment. International contributors working across a variety of sectors pinpoint the key topics facing the corporate information professionals today and share their experiences and expertise